PENINGKATAN PANGSA PASAR PADA PERUSAHAAN BODY LOTION MELALUI BRAND LOYALTY - Anita, Fitri; Sutrisno, Nuno (E-Jurnal Manajemen Trisakti School of Management (TSM), 2024)
This study tries to explain the effect of Brand Satisfcation through Emotional Brand Attachment and Brand Love on Brand Loyalty in Vaseline hand and body lotion users in Jakarta. The research design used is descriptive and causality research. Variables are measured using a 5 point Likert scale. This study uses primary data collected through questionnaires. Sampling in this study was purposive sampling using 231 respondents. This research data was processed using WarPLS SEM 8.0. The results of this study prove that Brand Satisfaction has an influence on Brand Loyalty through Emotional Brand Attachment and Brand Love. This research is expected to provide input or suggestions to hand and body lotion companies, especially the Vaseline company which is the object of this research, in order to increase market share in the hand and body lotion industry in Indonesia.